Midlife Crisis - G. Balamurugan; M. Vijayarani; G. Radhakrishnan (Indian Journal of Psychiatric Nursing)
Midlife is a pivotal stage of adulthood, characterized by biological, psychological, and social transitions that often lead to a “midlife crisis.” This phenomenon, while not universal, manifests as a period of self-reflection, reassessment, and potential turmoil, influenced by personal and societal factors. This paper explores the complexities of midlife, including its impact on mental health, relationships, careers, and overall well-being. Key themes include the transition through ego mastery stages, the interplay of physical health, mortality awareness, and evolving roles, as well as gender-specific experiences. While midlife crises may result in emotional upheaval and dissatisfaction, they also offer opportunities for growth and self-discovery. Coping strategies, such as reframing challenges, seeking support, and prioritizing physical activity, are highlighted as transformative tools. The role of healthcare professionals in normalizing this experience and fostering resilience is emphasized. Ultimately, this study underscores midlife as both a challenging and enriching phase, inviting further research into its nuanced dynamics..